Therapeutic mechanisms of ginseng in coronary heart disease - Tang, Miao-Miao; Zhao, Shu-Ting; Li, Ran-Qi; Hou, Wei (Frontiers in Pharmacology, 2023)
Coronary heart disease (CHD) is the most common clinical manifestation of cardiovascular disease. It is characterized by myocardial ischemia, which is caused by coronary atherosclerosis. CHD is a significant global health problem with increasing prevalence every year because of significant changes in the lifestyles and diets. Ginseng is a traditional Chinese medicinal herb that has been used in food preparations and traditional medicine for several centuries. Several studies have demonstrated that ginseng improved cardiac function by normalizing blood glucose levels and decreasing blood pressure, oxidative stress, platelet aggregation, and lipid dysregulation in vivo. This review describes the current understanding of the mechanisms by which ginseng alleviates CHD, and provides a reference for the clinical development and application of ginseng as an alternative therapy for CHD.